Preventive behavior against SARS-CoV-2 infection in adults according to whether or not they live with children. A combined analysis of the nationwide COSMO-SPAIN and ENE-COVID surveys - Imane Jroundi; Imane Jroundi; Nerea Fernández de Larrea-Baz; Nerea Fernández de Larrea-Baz; Carmen Rodríguez-Blázquez; Carmen Rodríguez-Blázquez; Roberto Pastor-Barriuso; Roberto Pastor-Barriuso; Marina Pollán-Santamaría; Marina Pollán-Santamaría; Maria João Forjaz; Maria João Forjaz; et al. (Frontiers Media S.A., 2023)
IntroductionThe protection of children is a major driver of behavior among those in charge of their care. We evaluated whether compliance with preventive measures against SARS-CoV-2 infection among adults living with children was different from that of those not living with them, in 2020.MethodsWe used the COSMO-SPAIN (N = 867) and the nationally representative ENE-COVID (N = 29,926) surveys to estimate prevalence of compliance (95% confidence interval). Logistic model based standardization methods were applied to estimate standardized prevalence differences (SPrD) to the overall distribution of age, sex, education, history of COVID-19, and residence of other >60 yrs in the household.ResultsWe observed that adults living with children more frequently avoided bars (SPrDENE−COVID: 4.2%; 95% CI: 2.3-6.1), crowded places (SPrDCOSMO: 8.0%; 95% CI: 0.6-15.1) and did not use public transportation (SPrDENE−COVID: 4.9%; 95% CI: 3.0-6.7). They were also more worried about work and family conciliation (SPrDCOSMO: 12.2%; 95% CI: 4.8-19.5) and about closure of education centers (SPrDCOSMO: 26.5%; 95% CI: 19.4-33.6).DiscussionIn general, adults living with children adopted slightly more frequently social distancing measures.